Theoretical foundations of the university policultural education - Bakhov, Ivan (My University, 2016)
In the context of justification pedagogical principles and functions of the university multicultural education trends analysis of multicultural education is given, the importance of the role of universities in the development of ulticultural education is accented. It defines connection of multicultural education to the problem of learning language as precondition for attracting to cultural values. У контексті обґрунтування педагогічних принципів і функцій університетської полікультурної освіти наведено аналіз напрямів розвитку полікультурної освіти, акцентовано увагу на значущості ролі університетів у становленні полікультурної освіти. Відзначено зв’язок полікультурної освіти з проблемою вивчення мови як передумови залучення до цінностей культур.
Keywords: multicultural education; мультикультурна освіта; pedagogical principles; педагогічні принципи; вивчення мови; language learning